2014
DOI: 10.5455/2349-3933.ijam20141107
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid - cost effective method in preventing blood loss in total knee replacement

Abstract: Background: Total joint replacement is a frequently done procedure in modern day practice of any orthopedics unit. Limiting blood loss both postoperatively and intraoperatively presents a challenge to the surgeon. Use of tranexamic acid (TA) reduces perioperative blood loss and need for allogenic blood transfusion in patients undergoing total knee replacement. Methods: This is a randomized controlled study that involved 105 patients who underwent primary total knee arthroplasty at our institute. A total of 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In both the studies the patients receiving tranexamic acid had a significant reduction in postoperative blood loss in comparison to the patients who were operated without tranexamic acid (1549 ±574 ml/ 847±356 ml and 1410 ± 480 ml/ 730 ± 280 ml, respectively). The average amount of blood loss in the drain has been found to vary with different authors with the highest reported by Sreehari et al (1828 ml/ 826 ml) and lowest reported by Krishnan et al (465 ±298 ml/296.7 ±195.6 ml) 16,18 . Though there is variation among the research in terms of the amount of the drain output there is a significant decrease of the post-operative blood loss in the patient with tranexamic acid 1,4 .…”
Section: Discussionmentioning
confidence: 97%
“…In both the studies the patients receiving tranexamic acid had a significant reduction in postoperative blood loss in comparison to the patients who were operated without tranexamic acid (1549 ±574 ml/ 847±356 ml and 1410 ± 480 ml/ 730 ± 280 ml, respectively). The average amount of blood loss in the drain has been found to vary with different authors with the highest reported by Sreehari et al (1828 ml/ 826 ml) and lowest reported by Krishnan et al (465 ±298 ml/296.7 ±195.6 ml) 16,18 . Though there is variation among the research in terms of the amount of the drain output there is a significant decrease of the post-operative blood loss in the patient with tranexamic acid 1,4 .…”
Section: Discussionmentioning
confidence: 97%